THE REPRESENTATION OF SHALOM MAWIRA'S RESISTANCE IN THE NOVEL PEREMPUAN YANG MENUNGGU DI LORONG MENUJU LAUT AND ITS RELEVANCE AS TEACHING MATERIAL - Adilla Wianti Sembiring, Adilla Wianti Sembiring; Esmeralda Estella br Sitepu, Esmeralda Estella br Sitepu; Nurul Hidayah, Nurul Hidayah; Sartika Sari, S.S.,M.Hum., Sartika Sari, S.S.,M.Hum.; Hilda Septriani, S.S.,M.Hum., Hilda Septriani, S.S.,M.Hum. (Jurnal Profesi Keguruan, 2024)
This study aims to analyze the representation of Shalom Mawira's resistance in the Novel "Perempuan Yang Menunggu Di Lorong Menuju Laut" by Dian Purnomo and its relevance as a teaching material at SMP Darussalam Medan. This novel tells the story of the struggle of Shalom Mawira, a Sangihe woman who fights to defend a gold mine that will be exploited by the Biongo company in her homeland, which is represented as a form of resistance against the government's injustice in handling this case. This study uses a qualitative approach with a descriptive-analytical method to describe and analyze the form of resistance carried out by Shalom Mawira and the Sangihe community and relate it to the Indonesian language learning curriculum. By utilizing gender studies, the study shows that Shalom Mawira's resistance in this novel depicts courage, solidarity, and determination in facing pressure and injustice. In terms of relevance, this novel can be used as teaching material at SMP Darussalam Medan because it has the potential to increase awareness of protecting the environment and foster a sense of nationalism in students. In addition, it can also be a means to train critical literacy and appreciation of local culture. This research provides theoretical contributions to the study of literature and education, as well as practical benefits for students and teachers. For students, this novel can be an interesting learning medium to understand social and cultural issues, while for teachers, this research offers alternative innovative and contextual teaching materials.